Desain Sistem Pendingin Inlet Air Turbin Gas Menggunakan Sistem Refrigerasi Absorpsi pada PLTGU - Burhanul Mustofa Mochamad; Endri Kusuma George; Nur Budiyanto Ekky (Proceedings Conference on Marine Engineering and its Application, 2018)
Gas and steam power plant (PLTGU) is a combined cycle between PLTG and PLTU. The parameters to be achieved in order for the PLTG system to work optimally are regulated in ISO 39772. The gas turbine can work optimally if the air temperature enters the compressor 15áµ’C, at 60% moisture and at a pressure of 101.3 kPa. But data from BMKG condition of environment in Gresik mean at temperature 32áµ’C at relative humidity 65% to 85%. Therefore a cooling system is required to cool the inlet air gas turbine. On the other hand the exhaust gas temperature from HRSG still high and can be utilized as the energy source of the absorption cooling system. From the results of balanced energy calculations obtained some results such as the amount of exhaust gases from HRSG of 52952 kW and the power required to cool the inlet air of 22365.65 kW. The result of exergy calculation obtained some results the biggest destroyed of energy in combustor amount of 287369 kW. Five absorption cooling machine LG type WC2N135 is arranged in parallel to achieved the power. When the turbine inlet temperature is 32Â°C the power is 125251,127 kW otherwise turbin inlet temperature is 15áµ’C the power is 139986,53 kW.